How to collaborate in building synergies among Muslim scholars, researchers, entrepreneurs, policy makers, governmental and non governmental organizations? - Kayadibi, Saim (2014)
This paper tries to find a manner to bring concrete solutions to clarify the deficiencies in the field where Muslim Ummah has been straggling since the couple of decades. In order to create appropriate solutions, every single new and senior researchers must fulfil their Ummatic responsibilities. For that reason, scholars, entrepreneurs, researchers, governmental or non-governmental organizations, policy makers, industries should create first a sustainable collaboration networks among them. The key word for creating a sustainable collaboration networks among Muslim countries is to build synergy among them. The Muslim Ummah urgently needs a new Mindset based on the eternal values and parameters which raise them into a level of civilization building metaphor. After exploring the current possible challenges among the scholars, entrepreneurs, researchers, governmental or non-governmental organizations, policy makers, industries, the paper will propose substantial and applicable strategy to build synergies in order to create a sustainable collaboration networks among them inshaAllah.